EVALUACIÓN DE UNA BACTERINA DE DOSIS ÚNICA CONTRA Mycoplasma hyopnemoniae EN PORCINOS DE MADRES NO VACUNADAS. - Flores J., Johana (2012)
The effect of a single dose bacterin against Mycoplasma hyopnemoniae on body weight gain, antibody titers, and degree of lung lesions in piglets from non-vaccinated dams reared in a pig farm with history of mycoplasmosis was evaluated. A total of 60 piglets of both sexes were distributed in a vaccinated and a control group. The bacterin was applied at 6 weeks of age. The frequency of seropositive animals and the antibody titers against M. hyopnemoniae were determined using serum samples collected at 3, 6, 10, 12, 16, and 21 weeks of age. Body weight gain (g/day) was calculated from body weight at weaning (19 days) and at slaughter (140 days).Antibody levelswere significantly higher at 10 and 13 weeks (p<0.05) in the vaccinated group, but similar from week 16 onwards, possibly due to the natural infection process in the control group. The level of lung lesions and number of affected animals was lower in the vaccinated group. It is concluded that the bacterin of a single dose had a positive effect against M. hyopnemoniae improving bodyweight gain.